2023
DOI: 10.3389/fpsyg.2023.1112711
|View full text |Cite
|
Sign up to set email alerts
|

Videoconferencing analytic psychodrama in treating young adults’ psychological suffering: preliminary results

Abstract: The study aims to explore the effects that videoconferencing Analytic Psychodrama (AP) has on the psychological wellbeing and emotional competence of young adults who are suffering from mental health problems. Twenty-two undergraduate students, asking for help at the Psychological Counselling Service of the University of Bologna for anxiety-depressive problems, took part in the three online groups that met weekly from October 2020 to July 2021. The Clinical Outcomes in Routine Evaluation Outcome Measure, the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Its efficacy in treating depression and anxiety is evident from the literature Bouchard et al, 2022;Giovanetti et al, 2022;Matsumoto et al, 2021). Some studies have shown promising results in cases of panic disorder, agoraphobia, post-traumatic stress disorder (PTSD), obsessive-compulsive disorder and substance use, and, not least, in improving general well-being (Biolcati et al, 2023;Bouchard et al, 2020;Lin et al, 2019;Matsumoto et al, 2021;Morland et al, 2010;Yurayat & Seechaliao, 2021). However, the literature also suggests some limits of VCP (APA, 2013(APA, , 2023Connolly et al, 2020;Tomaino et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Its efficacy in treating depression and anxiety is evident from the literature Bouchard et al, 2022;Giovanetti et al, 2022;Matsumoto et al, 2021). Some studies have shown promising results in cases of panic disorder, agoraphobia, post-traumatic stress disorder (PTSD), obsessive-compulsive disorder and substance use, and, not least, in improving general well-being (Biolcati et al, 2023;Bouchard et al, 2020;Lin et al, 2019;Matsumoto et al, 2021;Morland et al, 2010;Yurayat & Seechaliao, 2021). However, the literature also suggests some limits of VCP (APA, 2013(APA, , 2023Connolly et al, 2020;Tomaino et al, 2022).…”
Section: Introductionmentioning
confidence: 99%